Detection of Prokaryotes on the Astomatous Ciliated Protist Kentrophoros flavus (Ciliophora, Karyorelictea) Revealed A Consistently Associated Muribaculaceae-Like Bacterium - Bi, Luping; Zhang, Xiaoxin; Zou, Songbao; Ji, Daode; Zhang, Qianqian (Frontiers in Marine Science, 2022)
The interactions between symbiotic bacterial consortia and their protist hosts in benthic environments have attracted increasing interest in recent years. In the present study, we investigated the diversity of potentially associated bacteria for an astomatous ciliate, Kentrophoros flavus, collected in the intertidal zone of Yantai, China. For the first time, the diversity of the associated bacteria in the species K. flavus was examined using 16S rRNA-based techniques (clone libraries and PacBio sequencing) and the fluorescence in situ hybridization (FISH) technique. The 16S rRNA-based sequencing revealed a higher diversity of associated bacteria in K. flavus than previously expected. In addition to a genus-typical thiotrophic symbiont, the “Candidatus Kentron” stain YE, we provide evidence showing the consistent existence of one Muribaculaceae-like bacterium that was secondarily abundant among the bacterial operational taxonomic units (OTUs). Fluorescence in situ hybridization (FISH) with three specific probes and double-label FISH experiments with “Candidatus Kentron” probes showed that the Muribaculaceae-like bacterium was abundant and merged with the “Candidatus Kentron” stain YE on the cell surface of the host. A phylogenetic analysis of the bacterial 16S rRNA gene showed that the bacterium was a distinct branch in Muribaculaceae, members of which are primarily reported from gut microbiome. The name “Muribaculaceae-like bacterium associated with Kentrophoros flavus” (MLAKF) is proposed for the new bacterium. The higher 16S rRNA diversity in K. flavus and the discovery of MLAKF on the cell surface both suggest a potential bacterial consortium that interacts with the host K. flavus.